2007
DOI: 10.1104/pp.107.101980
|View full text |Cite
|
Sign up to set email alerts
|

AtREV1, a Y-Family DNA Polymerase in Arabidopsis, Has Deoxynucleotidyl Transferase Activity in Vitro

Abstract: To clarify the functions of the Arabidopsis thaliana REV1 (AtREV1) protein, we expressed it in Escherichia coli and purified it to near homogeneity. The deoxynucleotidyl transferase activity of the recombinant AtREV1 was examined in vitro using a primer extension assay. The recombinant AtREV1 transferred one or two nucleotides to the primer end. It efficiently inserted dCMP regardless of the opposite base. AtREV1 also inserted a dCMP opposite an apurinic/apyrimidinic site, which is physiologically generated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Reduction of the spontaneous mutation frequency in rev3-1 and rev1-1 indicates that AtPolz and AtRev1 are involved in spontaneous mutagenesis, as reported for yeast (Kalinowski et al, 1995;Harfe and Jinks-Robertson, 2000). In our previous report, we suggested that AtPolz and AtRev1 are involved in the bypass of apurinic/apyrimidinic sites that are generated under normal physiological conditions (Takahashi et al, 2007). Additionally, our preliminary results suggested the involvement of AtPolz and AtRev1 in g-rayinduced mutations (M. Nakagawa, S. Takahashi, A. Tanaka, I. Narumi, and A.N.…”
Section: Spontaneous and Other Mutation Sourcessupporting
confidence: 64%
See 4 more Smart Citations
“…Reduction of the spontaneous mutation frequency in rev3-1 and rev1-1 indicates that AtPolz and AtRev1 are involved in spontaneous mutagenesis, as reported for yeast (Kalinowski et al, 1995;Harfe and Jinks-Robertson, 2000). In our previous report, we suggested that AtPolz and AtRev1 are involved in the bypass of apurinic/apyrimidinic sites that are generated under normal physiological conditions (Takahashi et al, 2007). Additionally, our preliminary results suggested the involvement of AtPolz and AtRev1 in g-rayinduced mutations (M. Nakagawa, S. Takahashi, A. Tanaka, I. Narumi, and A.N.…”
Section: Spontaneous and Other Mutation Sourcessupporting
confidence: 64%
“…4A). It is conceivable that AtRev1 plays a role in recruiting other TLS-type polymerase(s) such as AtPolz, AtPolk, and AtPolh, thereby allowing these enzymes to perform the bypass of damaged DNA, as suggested in our previous report (Takahashi et al, 2007).…”
Section: Mutation Frequency In Rev1 Rev3 Double Mutantsmentioning
confidence: 93%
See 3 more Smart Citations